2009
DOI: 10.1590/s0004-28032009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of carcinoembryonic antigen distribution in tumor tissue of colorectal carcinoma

Abstract: -Context -Carcinoembryonic antigen (CEA) can be detected in colorectal tumor tissue but its role in the survival of patients remains controversial. Objective -To characterize the expression of tissue CEA using immunohistochemical staining in colorectal tumors and to analyze the relationship between this finding and preoperative plasmatic level of CEA, morphologic features and survival of patients operated with curative intent for colorectal carcinoma. Method -Forty-seven patients were included in the study: 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
9
1
1
Order By: Relevance
“…Although previous studies reported no relationship between serum CEA concentration and tissue CEA expression , we found that serum CEA concentrations were higher in patients with CEA‐positive than CEA‐negative tumours. The discrepancy may be due to differences in categorization of tissue CEA expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies reported no relationship between serum CEA concentration and tissue CEA expression , we found that serum CEA concentrations were higher in patients with CEA‐positive than CEA‐negative tumours. The discrepancy may be due to differences in categorization of tissue CEA expression.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the significance of CEA over-expression in CRC as a prognostic marker remains controversial. Despite several reports supporting a possible correlation between CEA expression in CRC and tumour spread or patient survival [164166], no definitive correlation has been established [163,167] and CEA has found little utility as a prognostic marker. However, the expression of CEA by disseminated tumour cells isolated from intra-peritoneal lavage was found to strongly correlate with advanced tumour stages and an extremely poor prognosis [168], consistent with the suggestion that CEA may enhance metastasis by functioning as an attachment factor for disseminated CRC cells [169].…”
Section: Cancer Cellsmentioning
confidence: 99%
“…Several studies reported no correlation between the grade of CEA expression in cancer tissue and the serum CEA level [17,19,20]. However, another study reported that the grade of CEA expression in cancer tissue is related to the serum CEA level [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a positive relation between CEA levels in cancer tissue and serum CEA levels [16], whereas others have found no relation between these variables [17,18,19,20]. Currently available findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%